More Than 100 Persistent Symptoms of SARS-CoV-2 (Long COVID): A Scoping Review - Hayes, Lawrence D.; Ingram, Joanne; Sculthorpe, Nicholas F. (Frontiers in Medicine, 2021)
Background: Persistent coronavirus disease 2019 (COVID-19) symptoms are increasingly well-reported in cohort studies and case series. Given the spread of the pandemic, number of individuals suffering from persistent symptoms, termed ‘long COVID', are significant. However, type and prevalence of symptoms are not well reported using systematic literature reviews. Objectives: In this scoping review of the literature, we aggregated type and prevalence of symptoms in people with long COVID. Eligibility Criteria: Original investigations concerning the name and prevalence of symptoms were considered in participants ≥4-weeks post-infection. Sources of Evidence: Four electronic databases [Medline, Web of Science, Scopus, and the Cochrane Central Register of Controlled Trials (CENTRAL)] were searched. Methods: A scoping review was conducted using the Arksey and O'Malley framework. Review selection and characterisation was performed by three independent reviewers using pretested forms. Results: Authors reviewed 2,711 titles and abstracts for inclusion with 152 selected for full-text review. 102 articles were subsequently removed as this did not meet inclusion criteria. Thus, fifty studies were analysed, 34 of which were described as cohort studies or prospective cohort studies, 14 were described as cross-sectional studies, one was described as a case control study, and one was described as a retrospective observational study. In total, >100 symptoms were identified and there was considerable heterogeneity in symptom prevalence and setting of study. Ten studies reported cardiovascular symptoms, four examined pulmonary symptoms, 25 reported respiratory symptoms, 24 reported pain-related symptoms, 21 reported fatigue, 16 reported general infection symptoms, 10 reported symptoms of psychological disorders, nine reported cognitive impairment, 31 reported a sensory impairment, seven reported a dermatological complaint, 11 reported a functional impairment, and 18 reported a symptom which did not fit into any of the above categories. Conclusion: Most studies report symptoms analogous to those apparent in acute COVID-19 infection (i.e., sensory impairment and respiratory symptoms). Yet, our data suggest a larger spectrum of symptoms, evidenced by >100 reported symptoms. Symptom prevalence varied significantly and was not explained by data collection approaches, study design or other methodological approaches, and may be related to unknown cohort-specific factors.